2015
DOI: 10.1016/j.envpol.2015.02.015
|View full text |Cite
|
Sign up to set email alerts
|

Sources, occurrence and predicted aquatic impact of legacy and contemporary pesticides in streams

Abstract: 11We couple current findings of pesticides in surface and groundwater to the history of pesticide usage, 12 focusing on the potential contribution of legacy pesticides to the predicted ecotoxicological impact on 13 benthic macroinvertebrates in headwater streams. Results suggest that groundwater, in addition to 14 precipitation and surface runoff, is an important source of pesticides (particularly legacy herbicides) 15 entering surface water. In addition to current-use active ingredients, legacy pesticides, me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
85
0
6

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 155 publications
(94 citation statements)
references
References 54 publications
3
85
0
6
Order By: Relevance
“…It has been concluded that glyphosate and AMPA often occur as run-off from fields originating from glyphosate-based herbicide application. These residues not only became ubiquitous or "pseudo-persistent" contaminants in surface water, in periods with increasing concentrations over the years (McKnight et al, 2015;Carvalho, 2017;Primost et al, 2017), but through surface waters they were shown to be able to reach the seas as well, as documented in Germany in the estuaries of the Baltic Sea (Skeff et al, 2015). Glyphosate and AMPA were also found at up to 2.5 and 0.48 µg/l in rain and up to 9.1 and 0.97 ng/m 3 in air, respectively in the USA in Mississippi, Iowa and Indiana States in 2004(Chang et al, 2011, where both have been identified in the same period as common surface water contaminants near agricultural fields (Majewski et al, 2014).…”
Section: Exposure To Glyphosate-environmental and Food Analysis Humamentioning
confidence: 99%
“…It has been concluded that glyphosate and AMPA often occur as run-off from fields originating from glyphosate-based herbicide application. These residues not only became ubiquitous or "pseudo-persistent" contaminants in surface water, in periods with increasing concentrations over the years (McKnight et al, 2015;Carvalho, 2017;Primost et al, 2017), but through surface waters they were shown to be able to reach the seas as well, as documented in Germany in the estuaries of the Baltic Sea (Skeff et al, 2015). Glyphosate and AMPA were also found at up to 2.5 and 0.48 µg/l in rain and up to 9.1 and 0.97 ng/m 3 in air, respectively in the USA in Mississippi, Iowa and Indiana States in 2004(Chang et al, 2011, where both have been identified in the same period as common surface water contaminants near agricultural fields (Majewski et al, 2014).…”
Section: Exposure To Glyphosate-environmental and Food Analysis Humamentioning
confidence: 99%
“…El-Mufleh et al (2013) showed that PAH are mainly sequestered in the unsoluble part of sediment organic matter (humin) [6]. Sediment bound pesticides were identified as the primary source for ecotoxicity, although in most papers this refers only to the extractable part of residues [6]. Anyway, it is obvious that sediment NER is a neglected research field which needs more attention.…”
Section: Laudation Andreas Schäffermentioning
confidence: 99%
“…For instance Luo et al stated that it is not sufficient to analyze just the extractable portions of brominated flame retardants in sediments but rather to characterize also the sequestered portions (type I NER, that might be remobilized) to get the full picture of contamination [5]. El-Mufleh et al (2013) showed that PAH are mainly sequestered in the unsoluble part of sediment organic matter (humin) [6]. Sediment bound pesticides were identified as the primary source for ecotoxicity, although in most papers this refers only to the extractable part of residues [6].…”
Section: Laudation Andreas Schäffermentioning
confidence: 99%
See 1 more Smart Citation
“…Most of the former correlative researches have been mainly focused on the conditions of relative higher antibiotic concentrations, and how these compounds affected the bacterial community in laboratory experiments, which strongly limited our understanding about the potential ecological impact of these antibiotics on actual aquatic ecosystems [49,50]. Hence in our study, high-throughput sequencing (HTS) combined with correlation network analysis to explore the co-occurrence/exclusion patterns and effects between antibiotics and the bacterial community in the actual estuary ecosystem, as well as the influences of these antibiotics on co-occurrence pattern of cyanobacterial and non-cyanobacterial taxa.…”
Section: Correlations Between Antibiotic Concentrations and Bacterialmentioning
confidence: 99%